From a Friend: You've Got to Watch This!: A Content Analysis of TV News Website Videos and Social Sharing Links. (June 2018) - Ware, Jennifer
Social sharing of news content through Twitter, Facebook, email, and other platforms is increasingly important to local television (TV) news stations. This article presents the results of a longitudinal content analysis of the prevalence and design of the automated social sharing tools presented next to timely, local news content on TV news websites between 2010 and 2015. While 93% of news websites now contain automated social sharing icons, approximately 36% of the social shares from these tools contain incorrect information or lead back to different content altogether. While social sharing options have increased since 2010, automated messages shared with the links, and link accuracy rates, remain relatively unchanged. As readers' social sharing of news stories becomes more important to the TV news industry's penetration into social media platforms, it is increasingly crucial to study these automated social tools and how they can serve as unintentional gatekeepers by sharing the wrong information.